(untitled) (CAHIERS MAGELLANES-NS, 2024)
The growth of sensor technology has been abundant so this technology can be utilized to expand the mobile health to the next level. This article mainly focuses on the integration of m-health and sensors used in the healthcare industry. The study explains about the sensors, its types, and uses in detailed manner.